(3GdOQhS GdeSJaGOI ef JLGQH GdEUdGM GdEbJUGOj GdeYJeOI Ydi UfOhb GdfbO GdOhdj GdeaGgje (B- (3GdfJGFL (B- (3GdOQhS s - (3Ydj SjO(B, (3ESeGYjds ((3GdEScfOQjI(B:s (3OGQ GdJYdje GdLGeYj(B,s, 2020)
(3JfGhd gPG GdcJGH JLGQH GdEUdGM GdGbJUGOj GdeYJeOI Ydi UfOhb GdfbO GdOhdj MjK JMOK ef NdGd aUhd OQGSJg Yf eaghe GdEUdGM GdGbJUGOj ef efXhQ GdeDSSGJ GdeGdjI GdOhdjI hGdGbJUGO GdGSdGej hCfhGYg, HGdGVGaI Gdi GdCUd GdJGQjNj ddEUdGM GdGbJUGOj hSeGJg hCgOGag aj GdOhd GdfGejI , hehLHGJ gPG GdGUdGM hGhdhjGJg heJWdHGJg, eY GSJQGJjLjI GdJMhd GdJOQjLj GdfGLM, haj GdCNjQ GdOQhS GdeSJaGOI ef JLGQH GdGUdGM GdeYJeOI Ydi UfOhb GdfbO GdOhdj(B.s
(3GdHHdjhZQGajG U(B.107s